Upper Cretaceous Crustacea from Mexico and Colombia: similar faunas and environments during Turonian times - Francisco J. Vega; Torrey Nyborg; Alexis Rojas-Briceño; Pedro Patarroyo; Javier Luque; Héctor Porras-Múzquiz; Wolfgang Stinnesbeck (Revista Mexicana de Ciencias Geológicas)
Nine taxa represent the crustacean component of the Turonian fauna from the Eagle Ford Group limestones and marls that crop out in several quarries, northwest of Múzquiz, Coahuila, Mexico. Three crustacean taxa are found in common with deposits of similar age and paleoenvironment of the San Rafael Formation of Colombia. Planktic foraminifera, ammonoids, inoceramid bivalves, fishes, marine reptiles, a pterosaur and plant remains were preserved in the Múzquiz quarries, in what has been interpreted as an anoxic, low energy bottom at a water depth of no less than 50 m. The cirriped Stramentum preserved on the ammonite Forresteria is described. Stomatopod remains of the family Pseudosculdidae are described, their incompleteness and poor preservation prevent their detailed identification. One species of scyllarid lobster is included. An indeterminant species of nephropid lobster is also part of this assemblage. Presence of Gourretia aquilae (Rathbun) new combination, confirms correlation with the Eagle Ford Group in Texas. A systematic and morphologic review is provided for Cenomanocarcinus vanstraeleni Stenzel, a species widely distributed during Turonian times, and based on morphologic features of the abdomen and its relationship with coxae, it is assigned to the Podotremata. Also, preservation of soft tissue is reported from C. vanstraeleni and the scyllarid lobster. The raninid Cretacoranina sp. cf. C. dichrous (Stenzel) is also reported. In addition, two raninid taxa are described, their poor preservation prevents more detailed identification. The flattened appendages of C. vanstraeleni and of the raninid species suggest a burrowing habit and/or active swimming.